2021
DOI: 10.4108/eai.30-11-2021.172305
|View full text |Cite
|
Sign up to set email alerts
|

Device Authentication Codes based on RF Fingerprinting using Deep Learning

Abstract: In this paper, we propose Device Authentication Code (DAC), a novel method for authenticating IoT devices with wireless interface, by exploiting their radio frequency (RF) signatures. The proposed DAC is based on RF fingerprinting, an information-theoretic method, feature learning, and the discriminatory power of deep learning. Specifically, an autoencoder is used to automatically extract features from the RF traces and the reconstruction error is used as the DAC, and this DAC is unique to each individual devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…[44] It has also been shown that complex-valued neural networks have potential in domains where the data is naturally represented with complex numbers, or the problem is complex by design. [45] Thus, using such complex networks could also potentially be better in dealing with quantum-mechanical problems, as quantum mechanics is inherently a complex-valued theory. However, it is typically not efficient to implement a complex-valued network on a classical digital computer as complex numbers have to be represented by two real numbers on the digital computer, [46] which increases the computationally expensive components of the neural network algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…[44] It has also been shown that complex-valued neural networks have potential in domains where the data is naturally represented with complex numbers, or the problem is complex by design. [45] Thus, using such complex networks could also potentially be better in dealing with quantum-mechanical problems, as quantum mechanics is inherently a complex-valued theory. However, it is typically not efficient to implement a complex-valued network on a classical digital computer as complex numbers have to be represented by two real numbers on the digital computer, [46] which increases the computationally expensive components of the neural network algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Alladi et al [2] introduce an authentication system based on a physical unclonable function. Bassey et al [3] discuss the use of authentication codes for an Internet of Things (IoT) device, and by leveraging the Kolmogorov-Smirnov test, it determines the legitimacy of the user of an IoT device.…”
Section: Introductionmentioning
confidence: 99%
“…The work in [10] has proposed a physical unclonable function (PUF)-based authentication framework. The work in [11] proposes authentication code for IoT device authentication. The Kolmogorov-Smirnov test is used to decide the legitimacy of device users.…”
Section: Introductionmentioning
confidence: 99%